2019
DOI: 10.1155/2019/4716482
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Common Mental Disorder as Predictors of Stunting among Children Aged 6-59 Months in Western Ethiopia: A Case-Control Study

Abstract: Background. Child malnutrition in low- and middle-income countries still continues to be an alarming. Africa and Asia bear the greatest share of all forms of malnutrition. The association between maternal common mental disorder and stunting has not been studied well even in developed countries; much less in developing countries and even the findings are conflicting. Thus, the purpose of the present research was to investigate the relationship of maternal common mental disorder and child stunting. Methods. Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
10
0
6
Order By: Relevance
“…Only one design that considered major depression diagnosis found association with chronic malnutrition in children at 3 and 6 months old (Adewuya et al, 2008). The relationship between children stunting and maternal depressive symptoms is evident with prevalence of chronic malnutrition around 20% to 40% (Anato et al, 2020; Black et al, 2009; Girma et al, 2019; Harpham et al, 2005; Nguyen et al, 2014; Stewart et al, 2008), like our nutritional proxy prevalence (28.6%). Just two longitudinal research from Bangladesh (Nasreen et al, 2013) and England (Husain et al, 2012) found nonsignificant findings with these variables.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Only one design that considered major depression diagnosis found association with chronic malnutrition in children at 3 and 6 months old (Adewuya et al, 2008). The relationship between children stunting and maternal depressive symptoms is evident with prevalence of chronic malnutrition around 20% to 40% (Anato et al, 2020; Black et al, 2009; Girma et al, 2019; Harpham et al, 2005; Nguyen et al, 2014; Stewart et al, 2008), like our nutritional proxy prevalence (28.6%). Just two longitudinal research from Bangladesh (Nasreen et al, 2013) and England (Husain et al, 2012) found nonsignificant findings with these variables.…”
Section: Discussionmentioning
confidence: 65%
“…T A B L E 4 Multivariable analysis between depressive symptoms in the mother and anaemia in the children, Peru 2015 malnutrition around 20% to 40% (Anato et al, 2020;Black et al, 2009;Girma et al, 2019;Harpham et al, 2005;Nguyen et al, 2014;Stewart et al, 2008), like our nutritional proxy prevalence (28.6%). Just two longitudinal research from Bangladesh (Nasreen et al, 2013) and England (Husain et al, 2012) found nonsignificant findings with these variables.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…For example, several epidemiological studies of mother-infant pairs in developing countries with high prevalence of childhood undernutrition revealed that there is high association between childhood growth failure and poor maternal mental health (Rahman, Lovel, Bunn, Iqbal, & Harrington, 2004;Ross et al, 2011;Surkan, Kennedy, Hurley, & Black, 2011). This association most likely exists because maternal depression interferes with maternal interest in offspring and emotional quality of nurturing, which limit the offspring from reaching maximum growth capacity (Girma, Fikadu, & Abdisa, 2019). The factors that mediate such relationship between postnatal growth failure and maternal behavior are not defined by one general mechanism, but most likely driven by multiple environmental parameters that contribute to optimal maternal-offspring interactions.…”
Section: Discussionmentioning
confidence: 99%